Cobalt carbonate and preparation method thereof, cobaltosic oxide and lithium ion battery
By controlling the grain size and specific surface area of cobalt carbonate, suitable cobalt tetroxide was prepared, and lithium cobalt oxide positive electrode material was prepared as a precursor, which solved the problem of insufficient electrochemical performance of existing materials and achieved structural stability and electrochemical performance. promote.
Patent Information
- Application Number
- CN202411522334.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
AI Technical Summary
The electrochemical properties of existing lithium cobalt oxide positive electrode materials are limited by the grain size and specific surface area of cobalt tetroxide, and there are problems of poor particle consistency and low sintering efficiency in the preparation process.
By controlling the grain size and specific surface area of cobalt carbonate, using co-precipitation reaction and multiple sintering processes, co-precipitation reaction and multiple sintering processes were prepared as a precursor. Lithium cobalt oxide positive electrode material.
The structural stability and electrochemical performance of lithium cobalt oxide cathode material have been improved, and excellent rate performance and cycle stability are provided.
Smart Images

Figure CN119461500A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery materials, and specifically relates to cobalt carbonate and a preparation method thereof, cobalt tetroxide and a lithium ion battery. Background Art
[0002] Lithium cobalt oxide positive electrode materials are often used in the 3C electronics field because of their high energy density, good cycle performance and rate performance, and easy synthesis. Lithium cobalt oxide materials are generally large single crystal particles, and the grain size of the single crystal particles will affect the electrical properties of lithium cobalt oxide positive electrode materials. In industrial production, lithium cobalt oxide materials are usually prepared by sintering cobalt oxide and lithium source, and cobalt oxide is mainly prepared by calcining cobalt carbonate synthesized by wet method.
[0003] Cobalt carbonate can be used to prepare cobalt tetroxide through a calcination process, so the physical and chemical properties of the precursor cobalt carbonate will have an important impact on the performance indicators of cobalt tetroxide. Similarly, as an important precursor of lithium cobalt oxide, the physical properties of cobalt tetroxide, such as structure, grain size, morphology, etc., will also be carried over to the lithium cobalt oxide positive electrode material and have a great impact on its electrical properties. Generally, when the grain size of cobalt tetroxide is small, its specific surface area is large. When it is subsequently mixed with a lithium source and converted into lithium cobalt oxide, the larger specific surface area will greatly increase the active sites of the precursor in contact with the lithium source, which makes the transmission path of lithium ions shorter and the diffusion rate faster, which helps to improve the charge and discharge rate of lithium batteries; however, if the grain size of cobalt tetroxide is too small, the mechanical strength of the particles will decrease, and it will be easy to break when sintered with the lithium source, which will make the consistency of the obtained lithium cobalt oxide particles worse, thereby affecting the electrochemical performance of lithium-ion batteries. Therefore, controlling the grain size of cobalt carbonate and cobalt oxide within an appropriate range is beneficial to the preparation of lithium cobalt oxide positive electrode materials with good particle consistency, excellent rate and cycle performance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a cobalt carbonate and a preparation method thereof, cobalt tetroxide and a lithium ion battery, aiming to provide a cobalt carbonate and cobalt tetroxide with a suitable grain size, so that the lithium cobalt oxide positive electrode material prepared with cobalt tetroxide as a precursor has good structural stability and better electrochemical performance.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a cobalt carbonate, wherein the grain size of the cobalt carbonate (104) crystal plane is 200-250 Å, and the median particle size Dv50 of the cobalt carbonate particles is 16-20 μm.
[0007] In a second aspect, the present invention provides a method for preparing cobalt carbonate, the preparation method comprising the following steps: The precipitant solution and the cobalt salt solution are added to the reactor containing the base liquid in parallel, and stirring is started at the same time to carry out a coprecipitation reaction, the flow rate of the cobalt salt solution is controlled to be 2-4 L / h, and the flow rate of the precipitant solution is controlled to maintain the reaction pH. When the volume of the material in the reactor reaches the target volume, a concentrator equipped with a titanium metal filter element with a pore size of 5-10 μm is turned on, and the material is continued to be fed for precipitation reaction, and the target volume of the material in the reactor is maintained until a cobalt carbonate slurry with a solid content of 1000-1200 g / L is obtained; the cobalt carbonate slurry is subjected to solid-liquid separation and washing to obtain cobalt carbonate.
[0008] In an alternative embodiment, the precipitating agent comprises at least one of sodium carbonate, potassium carbonate, ammonium bicarbonate and sodium bicarbonate.
[0009] In an optional embodiment, the molar concentration of the precipitant solution is 2.0-3.0 mol / L.
[0010] In an alternative embodiment, the cobalt salt comprises at least one of cobalt sulfate, cobalt nitrate and cobalt chloride.
[0011] In an optional embodiment, the molar concentration of the cobalt salt solution is 1.5-2.0 mol / L.
[0012] In an optional embodiment, the base liquid is a precipitant solution, and the volume of the base liquid is 10% to 20% of the volume of the reactor.
[0013] In an optional embodiment, the reaction pH is 7.2-7.8.
[0014] In an optional embodiment, the target volume is 80% to 96% of the reactor volume.
[0015] In an optional embodiment, the stirring speed is 80-200 r / min, the coprecipitation reaction temperature is 40-48° C., and the coprecipitation reaction time is 80-100 h.
[0016] In an optional embodiment, the solid-liquid separation and washing of the cobalt carbonate slurry includes pumping the cobalt carbonate slurry into a centrifuge to filter out the mother liquor and washing the solid with pure water.
[0017] In a third aspect, the present invention provides a cobalt oxide, wherein the cobalt oxide is prepared by first sintering the cobalt carbonate described in the first aspect, then mixing with a dopant and then sintering for a second time.
[0018] In an optional embodiment, the cobalt tetraoxide has one or more of the following characteristics: The grain size of cobalt tetroxide (311) crystal plane is 660~700Å; The median particle size Dv50 of cobalt tetroxide is 14~18 μm; The specific surface area of cobalt tetroxide is 2m 2 / g~6m 2 / g; The change rate of Dv50 of cobalt tetroxide after 50MPa pressing relative to Dv50 before pressing D% is 0.5%~3.0%.
[0019] In an optional embodiment, the first sintering temperature is 350-450° C., and the first sintering time is 1-2 hours.
[0020] In an alternative embodiment, the dopant includes at least one of titanium dioxide, zirconium oxide, magnesium oxide, and aluminum oxide.
[0021] In an optional embodiment, the cobalt carbonate is subjected to a first sintering to obtain a cobalt tetroxide precursor, and the mass ratio of the cobalt tetroxide precursor to the dopant is (600-1200):1.
[0022] In an optional embodiment, the second sintering temperature is 600-700° C., and the second sintering time is 3-4 hours.
[0023] In a fourth aspect, the present invention further provides a lithium cobalt oxide positive electrode material, wherein the lithium cobalt oxide positive electrode material is prepared by mixing and sintering the cobalt oxide described in the third aspect and a lithium source.
[0024] In a fifth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises a positive electrode plate, and the positive electrode plate comprises the lithium cobalt oxide positive electrode material as described in the fourth aspect.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The cobalt carbonate of the present invention has a suitable (104) crystal face grain size and a large specific surface area, and the cobalt oxide obtained using the cobalt carbonate as a precursor also has a suitable (311) crystal face grain size and specific surface area; the cobalt oxide has many active sites for reacting with the lithium source and the particles have high mechanical strength, and the lithium cobalt oxide material obtained using the cobalt carbonate as a precursor has a fast diffusion rate of lithium ions, thereby having better rate performance and cycle stability. (2) The present invention uses a large-aperture metal filter element for concentration when preparing cobalt carbonate, which increases the clearing flux and improves the filtration efficiency; a lower cobalt salt flow rate is used during the coprecipitation reaction to slow down the growth rate of cobalt carbonate grains, which can effectively avoid the individual nucleation of cobalt carbonate and improve the nuclear explosion problem in the later stage of the synthesis of large-particle cobalt carbonate. The present invention achieves the control of the grain size of the (104) crystal plane by changing the synthesis process conditions of cobalt carbonate. It is used as a precursor and first sintered, and then mixed with a dopant and sintered for a second time to obtain cobalt tetroxide with a suitable (311) crystal plane grain size. Among them, the doping element can be used as a grain growth regulator to regulate the solid-phase interface reaction between cobalt tetroxide crystals, and further promote the grain growth of cobalt tetroxide during the crystallization process.
[0026] Other aspects will be apparent upon reading and understanding the drawings and detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings are used to provide further understanding of the technical solution of this article and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of this article and do not constitute a limitation on the technical solution of this article.
[0028] Figure 1 This is a SEM image of cobalt tetroxide prepared in Example 1; Figure 2 This is a SEM image of cobalt tetroxide prepared in Comparative Example 1; Figure 3 The XRD pattern of cobalt carbonate prepared in Example 1; Figure 4 This is the XRD pattern of cobalt tetroxide prepared in Example 1. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present disclosure and should not be regarded as specific limitations of the present invention.
[0030] It should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturers are not specified, are all conventional products that can be purchased commercially.
[0031] In a first aspect, the present invention provides a cobalt carbonate, wherein the grain size of the cobalt carbonate (104) crystal plane is 200-250Å, and the median particle size Dv50 of the cobalt carbonate particles is 16-20 μm, where Dv50 is the particle size corresponding to 50% of the cumulative particle size distribution percentage based on volume statistics.
[0032] The grain size of cobalt carbonate on the (104) crystal plane was obtained by analyzing the X-ray diffraction (XRD) spectrum of cobalt carbonate and measuring the half-height width (HWHM) of the diffraction peak on the (104) crystal plane. β ) and obtain the corresponding diffraction angle (2θ=24-33°) at the (104) crystal plane, and calculate its grain size using the Scherrer formula.
[0033] In a second aspect, the present invention provides a method for preparing cobalt carbonate, the preparation method comprising the following steps: The precipitant solution and the cobalt salt solution are added to the reactor containing the base liquid in parallel, and stirring is started at the same time to carry out a coprecipitation reaction, the flow rate of the cobalt salt solution is controlled to be 2-4 L / h, and the flow rate of the precipitant solution is controlled to maintain the reaction pH. When the volume of the material in the reactor reaches the target volume, a concentrator equipped with a titanium metal filter element with a pore size of 5-10 μm is turned on, and the material is continued to be fed for precipitation reaction, and the target volume of the material in the reactor is maintained until a cobalt carbonate slurry with a solid content of 1000-1200 g / L is obtained; the cobalt carbonate slurry is subjected to solid-liquid separation and washing to obtain cobalt carbonate.
[0034] In some embodiments, the flow rate of the cobalt salt solution is 2~4 L / h, for example, it can be 2 L / h, 3 L / h or 4 L / h, and the molar concentration of the cobalt salt solution is 1.5~2.0 mol / L, for example, it can be 1.5 mol / L, 1.8 mol / L or 2.0 mol / L, but it is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0035] In some embodiments, the precipitant solution is prepared by dissolving a precipitant in deionized water, the precipitant includes at least one of sodium carbonate, potassium carbonate, ammonium bicarbonate and sodium bicarbonate, and the molar concentration of the precipitant solution is 2.0-3.0 mol / L, for example, it can be 2.0 mol / L, 2.5 mol / L or 3.0 mol / L, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0036] In some embodiments, the volume of the base liquid is 10% to 20% of the volume of the reactor, for example, it can be 10%, 15% or 20%, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0037] In some embodiments, the reaction pH is 7.2-7.8, for example, 7.2, 7.5 or 7.8, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0038] In some embodiments, the target volume is 80% to 96% of the reactor volume, for example, 80%, 85% or 96%, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0039] In some embodiments, the pore size of the titanium metal filter element used in the concentrator is 5-10 μm, for example, 5 μm, 7 μm or 10 μm, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0040] In some embodiments, the stirring speed is 80~200 r / min, for example, 80 r / min, 100 r / min or 200 r / min, the coprecipitation reaction temperature is 40~48°C, for example, 40°C, 44°C or 48°C, and the coprecipitation reaction time is 80~100h, for example, 80h, 90h or 100h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0041] In some embodiments, the solid-liquid separation and washing of the cobalt carbonate slurry includes pumping the cobalt carbonate slurry into a centrifuge to filter out the mother liquor, taking the solid and washing it with pure water for 3 to 5 times, for example, 3 times, 4 times or 5 times, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0042] The present invention increases the clearance flux and improves the filtration efficiency by using a large-aperture concentrator metal filter element during the synthesis of cobalt carbonate, thereby increasing the solid content of the cobalt carbonate slurry, and the higher solid content can increase the seed concentration of cobalt carbonate, thereby providing more nucleation sites, promoting the growth and growth of crystals, and further improving the crystallinity and regularity of cobalt carbonate crystals; in addition, the lower cobalt salt flow rate during the coprecipitation reaction slows down the growth rate of cobalt carbonate grains, and the number of cobalt carbonate nuclei generated per unit time is reduced, so that the nuclei can be fully adsorbed on the cobalt carbonate balls, which not only avoids the individual nucleation of cobalt carbonate, but also improves the problem of nucleus explosion in the later stage of synthesis of large-particle cobalt carbonate; therefore, by regulating the synthesis process conditions of cobalt carbonate, cobalt carbonate with a suitable (104) crystal face grain size range is obtained. If the grain size of cobalt carbonate is too small, its surface energy is too high, which can easily cause agglomeration of cobalt tetroxide particles during sintering; if the grain size of cobalt carbonate is too large, the solid phase diffusion process during sintering slows down, which limits the growth rate of cobalt tetroxide grains, resulting in the final cobalt tetroxide grain size being too small and having weak compressive strength.
[0043] In a third aspect, the present invention provides a cobalt oxide, wherein the cobalt oxide is prepared by first sintering cobalt carbonate having a (104) crystal plane grain size of 200-250 Å, and then mixing with a dopant and undergoing a second sintering.
[0044] The present invention performs the first sintering on cobalt carbonate with a high specific surface area and a small and suitable (104) crystal face grain size. During the sintering process, there is more space between the cobalt carbonate grains to move and rearrange, which increases the mutual contact and bonding between the particles and is conducive to the formation of an orderly and compact structure of the cobalt carbonate particles. This allows the grain size of the cobalt tetroxide precursor obtained after sintering to be initially regulated, and the particles also have a large number of microporous channels. The presence of the microporous channels increases the specific surface area of the cobalt tetroxide precursor, and the large specific surface area enables the surface of the cobalt tetroxide precursor to uniformly adsorb dopant molecules. In the subsequent second sintering process, the doping element can be used as a grain growth regulator to further regulate the solid phase interface reaction between cobalt tetroxide crystals, promote the grain growth during the cobalt tetroxide crystallization process, and then obtain a cobalt tetroxide material with a suitable (311) crystal face grain size range. If the grain size of the cobalt tetroxide material is too large, the active sites for reacting with the lithium source will be reduced, the reaction energy consumption will be increased, the migration rate of lithium ions in lithium cobalt oxide will be reduced, and the electrochemical reaction efficiency of the positive electrode material will be affected; if the grain size of the cobalt tetroxide material is too small, the mechanical strength of the particles will decrease, and the cobalt tetroxide particles will easily break during the subsequent sintering process, resulting in poor consistency of the prepared lithium cobalt oxide material particles.
[0045] In some embodiments, the grain size of the cobalt oxide on the (311) crystal plane is 660-700 Å.
[0046] In some embodiments, the median particle size Dv50 of the cobalt oxide is 14-18 μm.
[0047] In some embodiments, the specific surface area of the cobalt oxide is 2 m 2 / g~6m 2 / g.
[0048] In some embodiments, the change rate of Dv50 of the cobalt oxide after being pressed at 50 MPa relative to the Dv50 before pressing is D% is 0.5%~3.0%.
[0049] The grain size of cobalt oxide on the (311) crystal plane was obtained by analyzing the X-ray diffraction spectrum of cobalt oxide and measuring the half-height width of the diffraction peak on the (311) crystal plane ( β ) and obtain the corresponding diffraction angle at the (311) crystal plane (2θ=36-37°), and calculate its grain size using the Scherrer formula.
[0050] In some embodiments, the first sintering temperature is 350-450°C, for example, 350°C, 400°C or 450°C, and the first sintering time is 1-2h, for example, 1h, 1.5h or 2h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0051] In some embodiments, the cobalt carbonate is subjected to a first sintering to obtain a cobalt oxide precursor, the dopant includes at least one of titanium dioxide, zirconium oxide, magnesium oxide and aluminum oxide, and the mass ratio of the cobalt oxide precursor to the dopant is (600~1200):1, for example, it can be 600:1, 900:1 or 1200:1, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0052] The cobalt tetroxide material prepared by the present invention is doped with metal elements. The appropriate amount of element doping can not only regulate the grain size of cobalt tetroxide, but also improve the lithium ion diffusion coefficient of the lithium cobalt oxide material prepared therefrom, so that the positive electrode material has excellent electrochemical properties. If the element doping amount is too little, the grain size of the cobalt tetroxide material will be too large, and the migration rate of lithium ions will be slowed down, thereby making the electrochemical performance of the lithium cobalt oxide material poor; if the element doping amount is too much, the lattice strain of the cobalt tetroxide material will increase, which is not conducive to its use as a grain growth regulator to regulate the cobalt tetroxide crystallization process, and it is also difficult to control the grain size of the final product within the target range.
[0053] In some embodiments, the second sintering temperature is 600-700°C, for example, 600°C, 650°C or 700°C, and the second sintering time is 3-4h, for example, 3h, 3.5h or 4h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0054] In a fourth aspect, the present invention further provides a lithium cobalt oxide positive electrode material, wherein the lithium cobalt oxide positive electrode material is prepared by mixing and sintering the cobalt oxide described in the third aspect and a lithium source.
[0055] In a fifth aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The positive electrode sheet comprises the lithium cobalt oxide positive electrode material as described in the fourth aspect. The method for preparing the lithium-ion battery should be known to those skilled in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet can each be a sheet body, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a lithium-ion battery.
[0056] Specifically, the features and performances of the present invention are further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.
[0057] Example 1 This embodiment provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 16.2 μm; the grain size of the cobalt carbonate (104) crystal plane is 221 Å; the median particle size Dv50 of the cobalt oxide material is 14.3 μm; the grain size of the cobalt oxide material (311) crystal plane is 668 Å; and the titanium content in the cobalt oxide material is 998 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: (1) Prepare 2.0 mol / L cobalt chloride solution and 2.0 mol / L sodium carbonate solution respectively. 5 L of sodium carbonate solution (10% of the volume of the reactor) was added to a 50 L reactor as the base liquid, and a cobalt chloride solution and a sodium carbonate solution with a flow rate of 2 L / h were added to the reactor in parallel. At the same time, stirring was started and the stirring speed was adjusted to 200 r / min to carry out a coprecipitation reaction. The reaction temperature was controlled to be 40°C, and the pH value of the reaction was maintained at 7.2 by controlling the flow rate of the sodium carbonate solution. When the volume of the material in the reactor reached 40 L (80% of the volume of the reactor), a concentrator equipped with a titanium metal filter element with a pore size of 5 μm was turned on for concentration, and the coprecipitation reaction was continued. During the concentration, the cobalt chloride solution and the sodium carbonate solution were continuously introduced into the reactor, and the volume of the material in the reactor was kept stable at 40 L. When the total coprecipitation reaction time was as long as 90 h, a large-particle cobalt carbonate slurry with a solid content of 1070 g / L was obtained. The cobalt carbonate slurry was centrifuged to filter out the mother liquor, and the solid was washed with pure water 3 times to obtain a cobalt carbonate filter cake.
[0058] (2) The cobalt carbonate filter cake was placed in a rotary kiln for low-temperature drying and pre-sintering at a temperature of 350°C for 2 h to obtain a cobalt tetroxide precursor; the cobalt tetroxide precursor and titanium dioxide were mixed in a high-speed mixer for 30 min, wherein the mass ratio of M (cobalt tetroxide precursor): M (TiO 2 )=600:1, and then the mixture of the two is put into a rotary kiln for a second sintering at a temperature of 700°C and a sintering time of 3h to obtain large-particle cobalt tetroxide material.
[0059] Example 2 This embodiment provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 19.8 μm; the grain size of the cobalt carbonate (104) crystal plane is 243Å; the median particle size Dv50 of the cobalt oxide material is 17.6 μm; the grain size of the cobalt oxide material (311) crystal plane is 693Å; and the titanium content in the cobalt oxide material is 506 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: (1) Prepare 1.5 mol / L cobalt sulfate solution and 3.0 mol / L ammonium bicarbonate solution respectively. 10 L of ammonium bicarbonate solution (20% of the volume of the reactor) was added to a 50 L reactor as the bottom liquid, and a cobalt sulfate solution and an ammonium bicarbonate solution with a flow rate of 4 L / h were added to the reactor in parallel. At the same time, stirring was started and the stirring speed was adjusted to 80 r / min to carry out a coprecipitation reaction. The reaction temperature was controlled to be 48°C, and the pH value of the reaction was maintained at 7.8 by controlling the flow rate of the ammonium bicarbonate solution. When the volume of the material in the reactor reached 48 L (96% of the volume of the reactor), a concentrator equipped with a titanium metal filter element with a pore size of 10 μm was turned on for concentration, and the coprecipitation reaction was continued. During the concentration period, the cobalt sulfate solution and the ammonium bicarbonate solution were continuously introduced into the reactor, and the volume of the material in the reactor was kept stable at 48 L. When the total coprecipitation reaction time was up to 80 h, a large-particle cobalt carbonate slurry with a solid content of 1190 g / L was obtained. The cobalt carbonate slurry was centrifuged to filter out the mother liquor, and the solid was washed with pure water 5 times to obtain a cobalt carbonate filter cake.
[0060] (2) The cobalt carbonate filter cake was placed in a rotary kiln for low-temperature drying and pre-sintering at a temperature of 450°C for 1 h to obtain a cobalt tetroxide precursor; the cobalt tetroxide precursor and titanium dioxide were mixed in a high-speed mixer for 30 min, wherein the mass ratio of M (cobalt tetroxide precursor): M (TiO 2 )=1200:1, and then the mixture of the two is put into a rotary kiln for a second sintering at a temperature of 650°C and a sintering time of 3.5 h to obtain large-particle cobalt tetroxide material.
[0061] Example 3 This embodiment provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 20.0 μm; the grain size of the cobalt carbonate on the (104) crystal plane is 215Å; the median particle size Dv50 of the cobalt oxide material is 17.9 μm; the grain size of the cobalt oxide material on the (311) crystal plane is 686Å; and the titanium content in the cobalt oxide material is 665 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: (1) Prepare a 1.8 mol / L cobalt chloride solution and a 2.5 mol / L ammonium bicarbonate solution. 7.5 L of ammonium bicarbonate solution (15% of the volume of the reactor) was added to a 50 L reactor as the bottom liquid, and a cobalt chloride solution and an ammonium bicarbonate solution with a flow rate of 3 L / h were added to the reactor in parallel. At the same time, stirring was started and the stirring speed was adjusted to 100 r / min to carry out a coprecipitation reaction. The reaction temperature was controlled to be 44°C, and the pH value of the reaction was maintained at 7.5 by controlling the flow rate of the ammonium bicarbonate solution. When the volume of the material in the reactor reached 42.5 L (85% of the volume of the reactor), a concentrator equipped with a titanium metal filter element with a pore size of 7 μm was turned on for concentration, and the coprecipitation reaction was continued. During the concentration period, the cobalt chloride solution and the ammonium bicarbonate solution were continuously introduced into the reactor, and the volume of the material in the reactor was kept stable at 42.5 L. When the total coprecipitation reaction time was up to 100 h, a large-particle cobalt carbonate slurry with a solid content of 1200 g / L was obtained; the cobalt carbonate slurry was centrifuged to filter out the mother liquor, and the solid was washed with pure water 4 times to obtain a cobalt carbonate filter cake.
[0062] (2) The cobalt carbonate filter cake was placed in a rotary kiln for low-temperature drying and pre-sintering at a temperature of 400°C for 1.5 h to obtain a cobalt tetroxide precursor; the cobalt tetroxide precursor and titanium dioxide were mixed in a high-speed mixer for 30 min, wherein the mass ratio of M (cobalt tetroxide precursor): M (TiO 2 )=900:1, and then the mixture of the two is put into a rotary kiln for a second sintering at a temperature of 600°C and a sintering time of 4 h to obtain large-particle cobalt tetroxide material.
[0063] Example 4 This embodiment provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 20.0 μm; the grain size of the cobalt carbonate (104) crystal plane is 210 Å; the median particle size Dv50 of the cobalt oxide material is 17.9 μm; the grain size of the cobalt oxide material (311) crystal plane is 690 Å; and the titanium content in the cobalt oxide material is 668 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: The preparation steps are the same as those in Example 3, except that the flow rate of the cobalt chloride solution is 2.5 L / h.
[0064] Example 5 This embodiment provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 20.0 μm; the grain size of the cobalt carbonate (104) crystal plane is 240Å; the median particle size Dv50 of the cobalt oxide material is 17.8 μm; the grain size of the cobalt oxide material (311) crystal plane is 677Å; and the titanium content in the cobalt oxide material is 663 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: The preparation steps are the same as those in Example 3, except that the flow rate of the cobalt chloride solution is 3.5 L / h.
[0065] Example 6 This embodiment provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 20.0 μm; the grain size of the cobalt carbonate (104) crystal plane is 215 Å; the median particle size Dv50 of the cobalt oxide material is 17.6 μm; the grain size of the cobalt oxide material (311) crystal plane is 670 Å; and the titanium content in the cobalt oxide material is 798 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: The preparation steps are the same as those in Example 3, except that the mass ratio of the cobalt oxide precursor to titanium dioxide is M (cobalt oxide precursor): M (TiO 2 )=750:1.
[0066] Example 7 This embodiment provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 20.0 μm; the grain size of the cobalt carbonate (104) crystal plane is 215 Å; the median particle size Dv50 of the cobalt oxide material is 17.7 μm; the grain size of the cobalt oxide material (311) crystal plane is 697 Å; and the titanium content in the cobalt oxide material is 571 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: The preparation steps are the same as those in Example 3, except that the mass ratio of the cobalt oxide precursor to titanium dioxide is M (cobalt oxide precursor): M (TiO 2 )=1050:1.
[0067] Comparative Example 1 This comparative example provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 16.2 μm; the grain size of the cobalt carbonate (104) crystal plane is 221 Å; the median particle size Dv50 of the cobalt oxide material is 14.6 μm; the grain size of the cobalt oxide material (311) crystal plane is 635 Å; and the titanium content in the cobalt oxide material is 1510 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: The preparation steps are the same as those in Example 1, except that the mass ratio of the cobalt oxide precursor to titanium dioxide is M (cobalt oxide precursor): M (TiO 2 )=200:1.
[0068] Comparative Example 2 This comparative example provides a cobalt carbonate, cobalt oxide and a preparation method thereof. The median particle size Dv50 of the cobalt carbonate particles is 16.2 μm; the grain size of the cobalt carbonate (104) crystal plane is 221 Å; the median particle size Dv50 of the cobalt oxide material is 14.8 μm; the grain size of the cobalt oxide material (311) crystal plane is 723 Å; and the titanium content in the cobalt oxide material is 154 ppm. The preparation method of the cobalt carbonate and cobalt oxide materials comprises the following steps: The preparation steps are the same as those in Example 1, except that the mass ratio of the cobalt oxide precursor to titanium dioxide is M (cobalt oxide precursor): M (TiO 2 )=2000:1.
[0069] Comparative Example 3 This comparative example provides a cobalt carbonate and cobalt tetroxide. The median particle size Dv50 of the cobalt carbonate particles is 16.2 μm; the grain size of the cobalt carbonate (104) crystal plane is 221 Å; the median particle size Dv50 of the cobalt tetroxide particles is 14.7 μm; the grain size of the cobalt tetroxide (311) crystal plane is 740 Å; and the titanium content in the cobalt tetroxide is 0 ppm.
[0070] This comparative example provides a method for preparing cobalt carbonate and cobalt trioxide, which comprises the following steps: the same as the preparation steps in Example 1, except that titanium dioxide is not doped in step (2).
[0071] Performance testing: 1. Specific surface area, particle size and scanning electron microscope (SEM) test The specific surface area of cobalt oxide material was tested using SSA-7000 specific surface area analyzer; the particle size of cobalt carbonate and cobalt oxide material was tested using GSL-101BI laser particle size analyzer; and the microscopic morphology of cobalt carbonate and cobalt oxide material particles was analyzed using Zeiss scanning electron microscope.
[0072] 2. X-ray diffraction (XRD) test The D8 Advance X-ray diffraction was used to perform XRD tests on the prepared cobalt carbonate and cobalt tetroxide materials. The X-ray source used Kα rays from a copper target, with a wavelength of λ=1.54056Å, a scanning speed of 5° / min, and a scanning range of 10°~68°. The grain sizes of the cobalt carbonate (104) crystal plane and the cobalt tetroxide (311) crystal plane were calculated using the Scherrer formula. , k is a constant, taken as 0.89; half-height width ( β ) and the diffraction angle (θ) are obtained by analyzing the XRD spectrum. When this formula is used to calculate the grain size, the half-height width of the diffraction peak ( β ) are converted to radians for calculation.
[0073] 3. Hardness test The obtained cobalt oxide particles were subjected to a compressive mechanical strength test at 50 MPa, and the median particle size Dv50 of the particles before and after pressing was measured, and the Dv50 of the particles after pressing at 50 MPa was calculated. 2 50 relative to Dv before compression 1 Rate of change of 50 D% is calculated as follows:
[0074] 4. The cobalt oxide material prepared in the embodiment and the comparative example is made into a lithium cobalt oxide positive electrode material, and then the lithium cobalt oxide positive electrode material is assembled into a button cell and its electrochemical performance is evaluated, which specifically includes the following steps: (1) Preparation of lithium cobalt oxide positive electrode material Cobalt trioxide and lithium carbonate were mixed according to n (Co): n (Li) of 1:1.05, ground, dried, calcined at 1050°C for 30 hours, crushed, and sieved to obtain a lithium cobalt oxide positive electrode material.
[0075] (2) Preparation of button cells The lithium cobalt oxide positive electrode material, the conductive agent acetylene black and the adhesive polyvinylidene fluoride were uniformly mixed in N-methylpyrrolidone at a mass ratio of 92:4:4 to make a slurry, which was then coated on aluminum foil and dried in a vacuum drying oven. The positive electrode sheet was pressed by a tablet press. The negative electrode sheet was graphite, and the electrolyte was 1 mol / L lithium hexafluorophosphate-ethylene carbonate: dimethyl carbonate (LiPF 6-EC:DMC, the volume ratio of EC and DMC was 1:1), polypropylene porous membrane was used as separator, and the battery was assembled in an argon glove box.
[0076] (3) Electrochemical performance test The assembled button cell was subjected to electrochemical performance testing in the charge and discharge voltage range of 3.0-4.5V, the test temperature was 25°C, the charge and discharge were performed at 1C, and the cycle was 50 weeks.
[0077] The test results are shown in Tables 1 to 3.
[0078] Table 1
[0079] Table 2
[0080] Table 3
[0081] In the attached figure: The SEM image of the cobalt tetroxide material obtained in Example 1 is as follows: Figure 1 As shown in the figure, it can be seen that the cobalt oxide material particles are complete and have no small cores. The SEM image of the cobalt oxide material prepared in Comparative Example 1 is as follows Figure 2 As shown in the figure, it can be seen that the cobalt oxide material particles have obvious powdering phenomenon, which may be related to the excessive doping amount of titanium element.
[0082] The XRD patterns of cobalt carbonate and cobalt oxide obtained in Example 1 are as follows: Figure 3-4 As shown, cobalt carbonate ( Figure 3 ) The diffraction peak at 32.42° corresponds to the (104) crystal plane of cobalt carbonate, and the grain size is 221Å; cobalt tetraoxide ( Figure 4 ) The diffraction peak at 36.84° corresponds to the (311) crystal plane of cobalt tetroxide, and the grain size is 668 Å.
[0083] Table 1~3: The grain size of the cobalt oxide (311) crystal surface of Examples 1 to 7 is in the range of 660 to 700 Å. The cobalt oxide in this grain size range has good mechanical strength and high surface activity, and the electrochemical performance of the lithium cobalt oxide positive electrode material prepared therefrom is good. The grain size of the cobalt oxide (311) crystal surface of Comparative Example 1 is less than 660 Å, and the change rate of its Dv50 before and after pressing is The D% value is high, the mechanical properties are poor, and the electrochemical performance of the obtained lithium cobalt oxide positive electrode material is poor; the grain size of the cobalt oxide (311) crystal surface of comparative example 2-3 is greater than 700 Å, The D% value is low, indicating that its mechanical properties are good, but the excessively large grain size will lead to a decrease in the specific surface area of cobalt oxide, and the active sites will be greatly reduced during the subsequent reaction with the lithium source, so the specific capacity of the obtained lithium cobalt oxide positive electrode material is relatively low.
[0084] From the analysis of Example 3, Example 6-7 and Comparative Example 1-2, it can be obtained that in the preparation process of the cobalt oxide material of the present invention, under the same sintering process conditions, the amount of dopant titanium dioxide used will affect the grain size of the cobalt oxide material and the performance of its positive electrode material. If the amount of titanium dioxide added is too large, the grain size of the cobalt oxide material will be too small. The smaller grain size will increase the grain gap and the particle binding ability will deteriorate, further causing the surface of the product particles to be easy to de-powder; if the amount of titanium dioxide added is too small, the grain size of the cobalt oxide material will be too large, and the migration rate of lithium ions will be slowed down, all of which will cause the electrochemical performance of the prepared lithium cobalt oxide material to deteriorate (Comparative Example 1-2). However, the electrochemical performance of the lithium cobalt oxide material prepared within the titanium element doping amount range provided by the present invention is good (Examples 3, 6-7).
[0085] From the analysis of Examples 3 and 4-5, it can be concluded that during the preparation of the cobalt carbonate and cobalt oxide materials of the present invention, the flow rate of the cobalt salt solution will affect the growth rate of the cobalt carbonate grains. Generally, the smaller the flow rate of the cobalt salt solution, the smaller the grain size of the obtained cobalt carbonate. The smaller grain size can accelerate the growth rate of cobalt oxide during the sintering process, which is beneficial to increase the grain size of cobalt oxide and make it have good mechanical properties, further improving the structural stability and capacity retention rate of the obtained lithium cobalt oxide material.
[0086] From the analysis of Example 1 and Comparative Example 3, it can be seen that cobalt tetroxide is obtained in Comparative Example 3 without titanium dioxide doping. Compared with Example 1, the grain size of the (311) crystal plane of cobalt tetroxide obtained without titanium element doping is larger, which is not conducive to the improvement of its specific surface area, although it has good compressive strength ( The D% value is low), but the low specific surface area is not conducive to the uniform mixing of cobalt oxide and lithium salt, resulting in poor electrochemical performance of the obtained lithium cobalt oxide material.
[0087] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A cobalt carbonate, characterized in that The grain size of the cobalt carbonate (104) crystal plane is 200-250Å, and the median particle size Dv50 of the cobalt carbonate particles is 16-20 μm.
2. A method for preparing cobalt carbonate according to claim 1, characterized in that: The preparation method of cobalt carbonate comprises the following steps: adding a precipitant solution and a cobalt salt solution to a reactor containing a base liquid in parallel, starting stirring to perform a coprecipitation reaction, controlling the flow rate of the cobalt salt solution to 2-4 L / h, controlling the flow rate of the precipitant solution to maintain the reaction pH, and when the volume of the material in the reactor reaches a target volume, starting a concentrator equipped with a titanium metal filter element with a pore size of 5-10 μm, continuing to feed the material for precipitation reaction, and maintaining the target volume of the material in the reactor until a cobalt carbonate slurry with a solid content of 1000-1200 g / L is obtained; and performing solid-liquid separation and washing on the cobalt carbonate slurry to obtain cobalt carbonate.
3. The method for preparing cobalt carbonate according to claim 2, characterized in that: The precipitant comprises at least one of sodium carbonate, potassium carbonate, ammonium bicarbonate and sodium bicarbonate; And / or, the molar concentration of the precipitant solution is 2.0-3.0 mol / L.
4. The method for preparing cobalt carbonate according to claim 2, characterized in that: The cobalt salt includes at least one of cobalt sulfate, cobalt nitrate and cobalt chloride; And / or, the molar concentration of the cobalt salt solution is 1.5-2.0 mol / L; And / or, the base liquid is a precipitant solution, and the volume of the base liquid is 10% to 20% of the volume of the reactor; And / or, the reaction pH is 7.2-7.8; And / or, the target volume is 80% to 96% of the reactor volume.
5. The method for preparing cobalt carbonate according to claim 2, characterized in that: The stirring speed is 80-200 r / min, the coprecipitation reaction temperature is 40-48° C., and the coprecipitation reaction time is 80-100 h.
6. A cobalt trioxide, characterized in that: The cobalt trioxide is prepared by first sintering the cobalt carbonate described in claim 1, then mixing it with a dopant and then sintering it again.
7. The cobalt trioxide according to claim 6, characterized in that The cobalt oxide satisfies one or more of the following characteristics: Feature 1: The grain size of the cobalt tetroxide (311) crystal plane is 660-700 Å; Feature 2: The median particle size Dv50 of the cobalt oxide is 14-18 μm; Feature 3: The specific surface area of the cobalt oxide is 2~6m 2 / g; Feature 4: The change rate of Dv50 of the cobalt oxide after being pressed at 50 MPa relative to the Dv50 before pressing D% is 0.5%~3.0%.
8. The cobalt tetraoxide according to claim 6, characterized in that The first sintering temperature is 350-450° C., and the first sintering time is 1-2 hours; and / or, the dopant comprises at least one of titanium dioxide, zirconium oxide, magnesium oxide and aluminum oxide; And / or, the cobalt carbonate is subjected to a first sintering to obtain a cobalt tetroxide precursor, and the mass ratio of the cobalt tetroxide precursor to the dopant is (600-1200):1; And / or, the second sintering temperature is 600-700° C., and the second sintering time is 3-4 hours.
9. A lithium cobalt oxide positive electrode material, characterized in that: The lithium cobalt oxide positive electrode material is prepared by mixing and sintering the cobalt trioxide described in any one of claims 6 to 8 with a lithium source.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode plate, and the positive electrode plate comprises the lithium cobalt oxide positive electrode material as claimed in claim 9.
Citation Information
Cited By
Spherical cobaltosic oxide as well as preparation method and application thereof
CN120622551A
Cobaltosic oxide and preparation method thereof
CN120736568A
A tricobalt tetroxide and a preparation method thereof
CN120736568B
Cobaltosic oxide, cobalt carbonate and preparation method thereof, and lithium cobalt oxide positive electrode material
CN120922925A